Análise da conformidade de pavimentos de peças de concreto intertravado em função do processo de produção - Carvalho, Ana Beatriz Luna de (2012)
In the last years, we saw a great change in economic scenery in Brazil. With the economics growth, came the great construction in infrastructure , the pavement in concrete prefabricate (pavers) have been a solution to the big urban center, like Recife e Fortaleza, areas of intensive traffics, like Pecém harbor, in Ceará. To the pavers, there are two process of molding, the manual and with the mechanic. In the manual molding, the concrete is put in the mold with the employees, the form can be of metal, PVC or glass fiber, the concrete has a plastic consistent, result a smooth surface. In the mechanic process, resistance and durability of the pavers are obtained with machines that vibran and press, in this case there are a guarantee of the homogeneity of the concrete, the high mechanic resistance. This article aims , compare pavers with manual molding and pavers with mechanic process, the concrete resistance, wear and friction. The pavers of four manufacture, in the city of Fortaleza, has been testing. It was used the norm of ABNT 9780, about resistance of concrete of pavers, and ABNT NBR 12042, about wear and friction in inorganic material because there are no norm about wear and friction in pavers. After analysis of the results, the pavers with manual process do not reach the brazilian norm (ABNT), while the pavers in mechanics process has satisfactory results. This papers, will be help the government to decide which pavers they can buy in their construction.